Analysis of antithrombotic therapy of atrial fibrillation in international and Russian registries - O. V. Reshetko; A. V. Sokolov; N. V. Furman (Izdatelstvo OKI, 2019)
In the article the features of the organization of international and Russian registers of patients with atrial fibrillation (AF), the clinical and demographic characteristics of patients included in the registers, as well as the features of antithrombotic therapy of AF and its compliance with current clinical guidelines were observed. In a number of large randomized controlled trials (RCTs), not less effectiveness, and in some cases, the superiority of direct oral anticoagulants (DOACs) over warfarin, were proved in the prevention of ischemic insulin stroke patients with non-valvular AF with better safety profile and ease of use. However, the problem of the use of data obtained during RCTs in real clinical practice, for the solution of which medical registers are gaining much popularity, remains relevant. The article provides an analysis of 16 prospective multicenter international and Russian registers of patients with AF. For convenience of comparison, registers were divided into three groups in accordance with the features of the organization and inclusion criteria. Unambiguous conclusions were drawn about the incompatibility of the real clinical practice of antithrombotic therapy of AF with current clinical recommendations. Differences in the population of patients with AF in Russia compared with European countries were found, which led to the conclusion that insufficient detection of AF at the outpatient stage of diagnosis and the resulting inappropriate anticoagulant therapy aiming the prevention of stroke and ischemic complications take place, which may be due to the differences in the socioeconomic status of the regions and the characteristics of the organization of medical treatment and preventive care to the population.